Unemployment and Portfolio Choice: Does Persistence Matter? - Franziska M. Bremus; Vladimir N. Kuzin (Verein für Socialpolitik, 2010)
We use a realistically calibrated life cycle model of consumption and portfolio choice to study the effects of social security on the investment decisions of households for the European case. Our model is mainly based on the one developed by Cocco, Gomes and Maenhout (2005). We extend it by unemployment risk using Markov chains to model the transition between different employment states. In contrast to most models in the life cycle literature, our model allows for three different states, namely employment, short-term as well as long-term unemployment. This allows us to examine the effects of persistence in the unemployment process on portfolio choice. Our main findings are, first, that in case of short-term unemployment only, social security systems as those established in the EU are able to offset the negative impact of unemployment risk on the portfolio-share invested in risky assets. Second, the simulation results reveal that when allowing for long-term unemployment the equity-share is suppressed, especially for young investors. We show that this negative effect of unemployment is mainly driven by its persistence.
Keywords: D91; E21; H31; 330; precautionary savings; unemployment insurance; long-term unemployment; income uncertainty